An Overview of DNA Repair in Amyotrophic Lateral Sclerosis - Fabio Coppedè (The Scientific World Journal)
Amyotrophic lateral sclerosis (ALS), also known as motor neuron disease (MND), is an adult onset neurodegenerative disorder characterised by the degeneration of cortical and spinal cord motor neurons, resulting in progressive muscular weakness and death. Increasing evidence supports mitochondrial dysfunction and oxidative DNA damage in ALS motor neurons. Several DNA repair enzymes are activated following DNA damage to restore genome integrity, and impairments in DNA repair capabilities could contribute to motor neuron degeneration. After a brief description of the evidence of DNA damage in ALS, this paper focuses on the available data on DNA repair activity in ALS neuronal tissue and disease animal models. Moreover, biochemical and genetic data on DNA repair in ALS are discussed in light of similar findings in other neurodegenerative diseases.